Beneficial effects of dry bottom ash extraction and recycling in modern PCF power plants. (1st March 2018) - Ricci, Daniele; Bassetti, Fulvio; Savastano, Simone
Abstract: The article describes the operational experience of the first industrial application of the Magaldi Ash Recycling (MAR®) system. That installation was commissioned in 2007 at a 2 × 320 MW pulverized coal-fired (PCF) power plant in Italy. The MAR® system is a recycling process that transforms bottom ash into fly ash by returning the "dry" bottom ash to the boiler combustion chamber. The dry bottom ash is removed from beneath the boiler using the MAC® Magaldi Ash Cooler. This technology, with more than 200 installations worldwide on boilers generating more than 70, 000 MW, extracts and cools down the bottom ash by means of a small amount of ambient air. Then, the MAR® system conveys the ash back to the coal feeders where it is mixed with coal, milled and reintroduced into the furnace. The effects of the bottom ash reinjection, including the results of a 2-year site investigation, will be discussed in the present paper. The benefits of the MAR® system for PCF power plants are remarkable and can be summarized by the following achievements: 1. Conversion of all bottom ash into saleable fly ash. 2. Complete elimination of costs associated with bottom ash disposal or dedicated slurry system to a bottom ash pond. 3. LOI content reduction in fly ash due to the dilution effect of dry bottom ash (∼8% reduction on average). 4. Fly ash in compliance with international standards: EN 197-1 (cement) and EN 450-1 (concrete) in the EU. 5. Environment respect: mixing fly ash with cement, CO2 emissions decrease. Around 0.9 tons of CO2 are generated from the production of a ton of Portland cement.